Beispiel Nr: 15
$ \text{Gegeben: } \text{Nullstellen: } x_1\qquad x_2 \\ \text{Formefaktor: } a \\ \text{Gesucht: faktorisierte Form } y=a(x-x_1)(x-x_2) \\ \text{Allgemeine Form }y=ax^2+bx+c \\ \\ \text{Nullstellen - Faktorisierte Form}\\ \textbf{Gegeben:} \\ P(-1/0)\qquad Q(-2/0) \\\\ \\ \textbf{Rechnung:} \\ P(-1/0)\qquad Q(-2/0) \qquad a=3 \\ \text{Formfaktor a und Nullstellen in die faktorisierte Form einsetzen}\\ y=a(x-x_1)(x-x_2)\\ y=3(x+1)(x+2)\\ y=3(x^2- x \cdot \left(-2\right) +1\cdot x +\left(-1\right)\cdot \left(-2\right) )\\ y=3(x^2 +3 x+2) \\ y= 3x^2-9x+6 $